FRI0100 Prednisone (pred), azathioprine (aza) and cyclosporin a (csa) combination is effective for membranous lupus nephritis (mnl). (1st June 2001) - Li, EK; Tam, LS; Szeto, CC; Lai, FM; Wong, SM; Leung, CB; Wong, KC; Lui, SF
Abstract : Background: Objectives: Methods: 10 consecutive female patients with mean age 35 ¡Ó 10 years and the mean disease duration prior to the onset of the index episode of nephritis was 86 ¡Ó 85 months with pure MLN were treated with prednisolone, AZA and CSA for at least 12 months. CSA was tapered in stable patients by 18–24 months. All patients were followed for 3 years. Results: At 1 year, 4 patients achieved complete response as defined as serum albumin over 35 g/L, urinary protein less than 0.3 g/day and serum creatinine less than 30% above the baseline value and 3 achieved partial response. One patient developed agranulocytosis and alopecia totalis, another patient withdrawn at 6 months because of inefficacy, and one patient had no response at 1 year. For the responders, serum albumin increased from 22.8 ¡Ó 5.1 to 34.4 ¡Ó 2.7 mg/l, accompanied by reduction in urine protein from 5.6 ¡Ó 3.2 to 0.8 ¡Ó 0.8 g/day, while serum creatinine remained unchanged. Significant increase in serum albumin and sustained reduction in urine protein were noted from 3 months onward. Creatinine clearance showed significant improvement by the end of 1 year. Serum C3 normalised in 3 out of 6 patients, whereas anti – ds DNA antibodies became negative in 5 out of 6 patients. The mean prednisone dose reduced from 26.8 ¡Ó 5.5 to 5.7 ¡Ó 1.9 mg/day, the mean dose of CSA also reduced from 235.7 ¡Ó 24.4 to 132.1 ¡Ó 49.4 mg/day at the end of 1 year. Side effects included hypertension requiring additional anti-hypertensives in 4 patients, minor infections in 2 patients and leucopenia in 1 patient. CSA was tapered by the end of second year in 4 patients. At 3 years, 6 patients had sustained response, 2 patients developed renal relapse at 18 and 20 months. One patient reached end stage renal failure at 27 months. Conclusion: Combination therapy using prednisolone, AZA and CSA is well tolerated and is efficacious in the management of MLN, and may prevent relapse in patients after stopping CSA.